High efficiency transformation of Penicillium nalgiovense with integrative and autonomously replicating plasmids - Fierro, Francisco; Laich, Federico; Garcı́a-Rico, Ramón O.; Martı́n, Juan F. (International journal of food microbiology, 2004)
Penicillium nalgiovense is a filamentous fungus that is acquiring increasing biotechnological importance in the food industry due to its widespread use as starter culture for cured and fermented meat products. Strains of P. nalgiovense can be improved by genetic modification to remove the production of penicillin and other potentially hazardous secondary metabolites, to improve its capacity to control the growth of undesirable fungi and bacteria on the meat product, and other factors that contribute to the ripening of the product in order to get safer and better quality foods. Genetic manipulation of P. nalgiovense has been limited by the lack of molecular genetics tools that were available for this fungus, particularly for “self-cloning” avoiding the use of exogenous DNAs. In this article we describe a series of vectors, selectable markers and transformation methods that can be used for efficient transformation of P. nalgiovense, gene cloning and expression. A uridine auxotrophic P. nalgiovense mutant with an inactive pyrG gene has been isolated. The P. nalgiovense wild-type pyrG gene was cloned and sequenced, and vectors carrying the gene were shown to complement the pyrG mutant. Autonomously replicating plasmids carrying the AMA1 region from Aspergillus nidulans transformed P. nalgiovense very efficiently; these plasmids were shown to be maintained as stable extrachromosomal elements in P. nalgiovense and could be rescued in Escherichia coli. The mitotic stability of self-replicative AMA1 plasmids in P. nalgiovense was higher than that reported for Penicillium chrysogenum.